Study of the Repair Action and Mechanisms of a Moisturizing Cream on an SLS-Damaged Skin Model Using Two-Photon Microscopy - Yixin Shen; Ying Ye; Lina Wang; Huiping Hu; Caixia Wang; Yuxuan Wu; Dingqiao Lin; Jiaqi Shen; Hong Zhang; Yanan Li; Peiwen Sun (Cosmetics)
This study evaluates the efficacy of a novel moisturizing cream using a sodium lauryl sulfate (SLS)-induced skin damage model, supported by advanced imaging with two-photon microscopy (TPM). TPM’s capabilities allow for in-depth, non-invasive visualization of skin repair processes, surpassing traditional imaging methods. The innovative formulation of the cream includes ceramide NP, ceramide NS, ceramide AP, lactobacillus/soybean ferment extract, and bacillus ferment, targeting the enhancement of skin hydration, barrier function, and structural integrity. In SLS-stimulated 3D skin models and clinical settings, the cream significantly improved the expression of key barrier proteins such as filaggrin (FLG), loricrin (LOR), and transglutaminase 1 (TGM1), while reducing inflammatory markers like IL-1α, TNF-α, and PGE2. Notably, the cream facilitated a significant increase in epidermal thickness and improved the dermal–epidermal junction index (DEJI), as observed through TPM, indicating profound skin repair and enhanced barrier functionality. Clinical trials further demonstrated the cream’s reparative effects, significantly reducing symptoms in participants with sensitive skin and post-intense pulsed light (IPL) treatment scenarios. This study highlights the utility of TPM as a groundbreaking tool in cosmetic dermatology, offering real-time analysis of the effects of skincare products on skin structure and function.